THE ROLE OF THE AMICUS CURIAE (FRIEND OF THE COURT) INSTITUTE IN THE FIELD OF LAW - Sh.Kh.Mamatalieva (Galaxy International Interdisciplinary Research Journal, 2021)
Amicus curiae, or "friend of the court" is a legal institution, the evolutionary development of which dates back to the times of Roman law and was continued in the legal systems of the family of Anglo-American law, is widely used today in international public and international private law.